QUASI-DISTRIBUTED FIBER-OPTIC RECIRCULATING SYSTEM FOR TEMPERATURE MEASUREMENT BASED ON WAVELENGTH-DIVISION MULTIPLEXING TECHNOLOGIES - A. V. Polyakov; T. D. Prokopenkova (Приборы и методы измерений)
Providing quality and reliable operation as well as temperature monitoring of modern systems are directly related on the use of innovative fiber optic technology based on the concept of so-called distributed and quasi-distributed sensors having large linear dimensions, in which the optical fiber is both sensor and data channel. Existing fiber optic sensors based on stimulated Raman scattering and stimulated Brillouin scattering have relatively high measurement error, long and complicated measurement method, high cost. The purpose of this paper was to develop an automated quasi-distributed fiber optic recirculating temperature measurement system using wavelength division multiplexing technology. Measurement method based on the registration arising due to temperature changes of the frequency of single optical pulses recirculating at adjacent wavelengths. Thus there is a periodic signal restoration on waveform, amplitude and duration. The sensing element is a segment of a multimode silica fiber coated with metal, separated spectrally selective elements, which are mainly offered to use dichroic mirrors. With the help of the developed mathematical model that takes into account the temperature dependence of the coefficient of linear expansion and Young’s modulus of the fiber, the spectral and temperature dependence of the refractive index, the chemical composition of the fibers, the type of metal coating system response function was calculated, which allows to evaluate the sensitivity and measurement accuracy. These studies determined: number of measuring sections (8), the maximal measured temperature (500 °C), the sensitivity (3,28 Hz/°C), the measurement error (±0,2 °C), and the optimum beginning time measurement after starting circulation (15 min), and counting time of the frequency meter (1 s). Carried out estimations have shown that the proposed measuring system can outperform existing analogues on set specifications.